Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine [tex]\((f+g)(x)\)[/tex] given the functions [tex]\( f(x) = x^2 - 3x - 4 \)[/tex] and [tex]\( g(x) = x^2 + x \)[/tex], we need to sum these two functions.
Starting with the functions:
[tex]\[ f(x) = x^2 - 3x - 4 \][/tex]
[tex]\[ g(x) = x^2 + x \][/tex]
Now, let's find [tex]\((f + g)(x)\)[/tex]:
[tex]\[ (f + g)(x) = f(x) + g(x) \][/tex]
[tex]\[ (f + g)(x) = (x^2 - 3x - 4) + (x^2 + x) \][/tex]
Next, we combine like terms:
[tex]\[ (f + g)(x) = x^2 + x^2 - 3x + x - 4 \][/tex]
[tex]\[ (f + g)(x) = 2x^2 - 2x - 4 \][/tex]
So, the function [tex]\((f + g)(x)\)[/tex] simplifies to:
[tex]\[ 2x^2 - 2x - 4 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{2 x^2 - 2 x - 4} \][/tex]
Starting with the functions:
[tex]\[ f(x) = x^2 - 3x - 4 \][/tex]
[tex]\[ g(x) = x^2 + x \][/tex]
Now, let's find [tex]\((f + g)(x)\)[/tex]:
[tex]\[ (f + g)(x) = f(x) + g(x) \][/tex]
[tex]\[ (f + g)(x) = (x^2 - 3x - 4) + (x^2 + x) \][/tex]
Next, we combine like terms:
[tex]\[ (f + g)(x) = x^2 + x^2 - 3x + x - 4 \][/tex]
[tex]\[ (f + g)(x) = 2x^2 - 2x - 4 \][/tex]
So, the function [tex]\((f + g)(x)\)[/tex] simplifies to:
[tex]\[ 2x^2 - 2x - 4 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{2 x^2 - 2 x - 4} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.